Pengembangan Aplikasi Mobile Social Crowdsourcing dan Early Warning Bencana Alam dengan menggunakan Push Notification - Rizqi Aryansa; Adam Hendra Brata; Herman Tolle (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Disaster is an event that can cause the destruction of society due to natural or human factors, it can cause impacts such as environmental damage, loss of life, property and psychological. The high number of natural disasters in Indonesia is a serious problem that must be resolved immediately to overcome the problem of disasters. With the development of mobile technology that accelerates, the use of technology that can be used by the public to share information about disasters, share information about locations and geospatial information using geotagging features and push notifications in real time. In addition, applications that use the Android platform will be developed in this study (Kitana) using crowdsourcing feature where disaster information can be immediately disbursed from other users. And use the BMKG API (Application Programming Interface) for disaster information. The technique used in this study is prototyping. Furthermore, the tests carried out are validation, unit testing, usability testing using SUS (System Usability Scale) as an instrument, and testing the performance of the push notification feature. Functional testing's results are valid and the application runs according to the user needs. Usability testing that produces a value of 73.5 where the value includes both good and successful categories. While the performance test of 10 test cases produces an average value of 1.6103 seconds, which means the system meets the real time criteria.